Artificial Intelligence and Algorithms in Intelligent Systems Proceedings of 7th Computer Science On-line Conference 2018, Volume 2 - Silhavy, Radek (Advances in Intelligent Systems and Computing,, 2019)
This book presents the latest trends and approaches in artificial intelligence research and its application to intelligent systems. It discusses hybridization of algorithms, new trends in neural networks, optimisation algorithms and real-life issues related to the application of artificial methods. The book constitutes the second volume of the refereed proceedings of the Artificial Intelligence and Algorithms in Intelligent Systems of the 7th Computer Science On-line Conference 2018 (CSOC 2018), held online in April 2018.